Марсианские войны: [Для семейн. чтения] / Э. Берроуз - Берроуз Эдгар Райс (Приключения и фантастика)
Экземпляры: БИС Р Удмуртия () / Инвентарный номер: / Цена: / Авт.знак: Б 51 / ГРНТИ: 17.82.93 / ББК: Ш9(2)72(7США)